Unraveling The Dynamics Price Volatility and Risk of Live Broiler Chicken in Jawa Tengah Province - Mutia Ayu Safitri; Suryantini, Any; Irham (Jurnal Manajemen dan Agribisnis, 2024)
Background: Jawa Tengah Province is one of the main broiler production centers in Indonesia, but fluctuations in live chicken prices in this area remain a big problem for farmers.Purpose: This study aims to (1) determine the volatility of live broiler chicken prices in Jawa Tengah Province, and (2) understand the level of price risk for live broiler chickens in Jawa Tengah Province.Design/methodology/approach: This research uses secondary time series data from January 2016 to February 2024 with ARCH-GARCH (Autoregressive Conditional Heteroskedasticity and Generalized Autoregressive Conditional Heteroskedasticity) and CCV (Conditional Coefficient Variance) analysis tools.Finding/Result: The results showed that (1) the volatility of broiler prices in Jawa Tengah Province is influenced by the variance and volatility of the previous period, and (2) the level of risk of broiler prices in Jawa Tengah Province is low.Conclusion: To estimate the price of live broilers in Jawa Tengah province in the next period the price reference used is the previous period broiler price data and farmers can produce broilers with an independent system.Originality/value: This study uses CCV (Conditional Coefficient Variance) to describe market risk from two perspectives, namely producers and consumers. Keywords: price reference, price risk, live broiler chicken, ARCH-GARCH, CCV